4(6y-5) - (3y+9) Please explain it to me. Thank you

4(6y-5) - (3y+9)=0

open the brackets by simple multiplication,

24y-20-3y-9=0

do simple addition subtraction, it'll come up

21y-29=0

this is the simplified form of the equation and if the value of y is to be determined, then

y=29/21

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up